Transglutaminase 2 expression is increased as a function of malignancy grade and negatively regulates cell growth in meningioma. - Yin-Cheng Huang; Kuo-Chen Wei; Chen-Nen Chang; Pin-Yuan Chen; Peng-Wei Hsu; Carl P Chen; Chin-Song Lu; Hung-Li Wang; David H Gutmann; Tu-Hsueh Yeh (PLoS ONE, 2014)
Most meningiomas are benign, but some clinical-aggressive tumors exhibit brain invasion and cannot be resected without significant complications. To identify molecular markers for these clinically-aggressive meningiomas, we performed microarray analyses on 24 primary cultures from 21 meningiomas and 3 arachnoid membranes. Using this approach, increased transglutaminase 2 (TGM2) expression was observed, which was subsequently validated in an independent set of 82 meningiomas by immunohistochemistry. Importantly, the TGM2 expression level was associated with increasing WHO malignancy grade as well as meningioma recurrence. Inhibition of TGM2 function by siRNA or cystamine induced meningioma cell death, which was associated with reduced AKT phosphorylation and caspase-3 activation. Collectively, these findings suggest that TGM2 expression increases as a function of malignancy grade and tumor recurrence and that inhibition of TGM2 reduces meningioma cell growth.